KNOWLEDGE AND AWARENESS REGARDING 3D PRINTING IN THE TREATMENT PLANNING OF ORTHOGNATHIC SURGERIES AMONG DENTAL PRACTITIONERS AND STUDENTS IN SAUDI ARABIA (CAHIERS MAGELLANES-NS, 2024)
Background: Dentistry has made extensive use of three-dimensional (3D) imaging to enhance diagnosis, treatment planning, and appliance production. With the advancement of 3D modeling and imaging technologies like CBCT, intraoral scanning, and CAD/CAM, technology has become more and more significant. Assessing dental professionals' knowledge and awareness regarding 3D printing in the treatment planning in Saudi Arabia is made easier, faster, and more trustworthy by the more accurate and realistic diagnostic information that 3D imaging offers on craniofacial hard and soft tissue.Objective: This Study aimed to evaluate Knowledge and awareness regarding 3D printing in the treatment planning of orthognathic surgeries among dental practitioners and students in Saudi Arabia. Methods: A Google Forms online survey with twenty questions. The questions were sent to specialist, Resident, General Dentist, Dental intern, and Dental students, were carried in various regions and communities across the Kingdom of Saudi Arabia. The following tests were used to examine the data: The questionnaire was validated through pilot testing. Microsoft Excel sheet. For statistical analysis, the Statistical Package for the Social Sciences (SPSS) Software version 20.0 (IBM Corp., USA) was used.Results: Regarding the knowledge and awareness of 3D printing technology, a significant 89.2% out of 418 participants were aware of digital technology in dentistry, with 81.8% acknowledging the applications of 3D printing, particularly regarding its use in Invisalign aligners. However, 38.5% reported lacking knowledge of current 3D printing technologies, indicating a gap in awareness. A notable 88.5% preferred 3D printing over traditional methods, while 90% advocated for increased education on this subject in dental curricula. Primary knowledge sources included academic institutions (60.5%) and social media (51.9%). Barriers to implementation were identified as equipment costs (40.9%) and lack of awareness (32.3%). A large majority (66.7%) acknowledged the benefits of 3D-printed mock surgeries for surgical accuracy, and 78.7% showed interest in further exploring 3D printing applications in dentistry, reflecting a positive outlook on its integration into dental practices.Conclusion: the study highlighted a significant awareness among dental practitioners and students in Saudi Arabia regarding the applications and advantages of 3D printing technology in orthognathic surgery. With 89.2% of participants familiar with digital technologies, including a strong preference for 3D printing over traditional methods, it is evident that there is a positive outlook towards integrating these modern practices into dental care. However, a notable gap remains, as 38.5% of individuals reported lacking knowledge of current 3D printing technologies.